Exploring Personality Traits in Elite Sport Players and Associate with a Good Project Managers - Kateřina Bočková; Slávka Čepelová (Emerging Science Journal, 2023)
The paper deals with the issue of personality in the context of the professions of an elite tennis player and a project manager. The objective of the conducted research is to find a set of personality characteristics typical for tennis and project management and to find out which personality characteristics of the analyzed professions are similar, or different. To confirm the hypothesis H: "The personality characteristics of an elite tennis player correspond to the demands of his profession, just as the personality characteristics of a project manager correspond to the demands of his profession, and there is demonstrably a correlation in the personality characteristics of elite tennis players and project managers, which corresponds to a correlation in the demands of these two professions," we will use the Cattell's 16 Personality Factor Test, the Spearman correlation analysis, the evaluation of the relevant test indicators difference in statistical significance using the Student t-test, and the comparative analysis. A comparison of the demands of the analyzed professions on a person and a comparison of the personality characteristics of the elite tennis players and the project managers results in the conclusion that the personalities of an elite tennis player and a project manager are somewhat similar, as well as a striking difference between them in the emotional area. The hypothesis was confirmed. An elite tennis player can be a good project manager. Doi: 10.28991/ESJ-2023-07-04-019 Full Text: PDF